Exercise behavior, practice, injury, and symptoms of respiratory tract infection of 502 Brazilian adults during lockdown oscillations in two years (2021-2022) of the COVID-19 pandemic - Lucas Guilherme Oliveira da Silva; Tatiane Silva de Souza; Camila Réquia Silva; Flávia Figueiredo Freua; Lucas Barqueiro Medeiro da Silva; Yara Juliano; Luiz Henrique Silva Nali; Luiz Carlos Hespanhol; Ana Paula Ribeiro (BMC, 2023)
Abstract Background In the period between 2020 and 2023, during the COVID-19 (coronavirus disease 2019) pandemic, many countries released their restriction measures so that individuals were able to begin practicing physical exercises and outdoor sports again. The purpose of the current study was to evaluate the physical exercise behavior, symptoms of respiratory tract infection, and training practice, as well as aspects of pain and injuries in the lower limbs of adults during periods of lockdown oscillations in the two years of the COVID-19 pandemic in Brazil. Methods Cross-sectional study. Participants: A total of 502 adults were evaluated during two consecutive years of the COVID-19 pandemic, corresponding to the years 2021 and 2022. A virtual questionnaire was applied using the Google Forms platform through a link, or a Quick Response Code available in social media environments. The variables collected were: anthropometric characteristics, presence of comorbidities, clinical history for the diagnosis of COVID-19, and behavior related to physical exercise practices, divided into five topics: (1) physical exercise habits; (2) symptoms and health care utilization; (3) habit of practicing physical exercise in relation to the prevention of COVID-19; (4) preventive measures for COVID-19; and (5) feelings and reasons for practicing exercises. Results A total 79.0% of the participants returned to the practice of physical exercise after a period of social isolation due to COVID-19, with running (30.0%) and muscle strength training (50.0%) being the most prevalent modalities, in which 62.0% of practitioners carried out the activity individually, without any professional or technical monitoring. With regard to physical preparation, 61.0% reported performing pre-training stretching, 64.0% associated with muscular resistance training. Of these, 89% did not report current injuries or pain symptoms when returning to exercise (69.0%). Total of 60.5% reported experiencing respiratory tract symptoms of COVID-19 and seeking a consultation with a doctor, and 61.0% performed diagnostic test, with RT-PCR (Real time-polymerase chain reaction) being the most common test. Of those tested, 55.0% were positive for COVID-19, without the need for hospitalization (95.0%). The most commonly used measures for the prevention of COVID-19 were the fabric or surgical mask. The predominant feeling in the pandemic was anxiety (50.5%) and the reasons for practicing sports were: physical conditioning (30.9%), a feeling of pleasure (21.3%), and weight loss (20.3%). Conclusion After two years of the COVID-19 pandemic (2021-2022), with periods of lockdown, there were low reports of injuries and pain symptoms after exercising on the return to physical exercise practices of running and strength training. However, the restrictions negatively affected the exercise behavior due to respiratory tract symptoms of COVID-19 and a reduction in training intensity, performed without any professional or technical supervision. The participants reported the use of a fabric or surgical mask for the prevention of COVID-19, and an increased feeling of anxiety. The reasons given for practicing physical exercise were physical conditioning, a feeling of pleasure, and weight loss.